Design and Development of Solar-Powered Water Pump Installation for the Tauno Village Community, Oba Tengah District, Tidore Kepulauan City - Suparman; Rahman, M. Natsir; Kabir, Fahyudi (Universitas Panca Marga, 2024)
Water is a fundamental human necessity, essential for daily activities such as drinking and cooking. However, access to water can be problematic, especially in areas where water sources are limited or groundwater is far from residential areas. Although various water pumps are now readily availab le, the challenge often lies in the availability of power sources. Fortunately, in tropical regions, sunlight is freely available year round. To generate electricity, sunlight must first be converted through an energy conversion process before it can be used to power devices such as water pumps. Therefore, it is necessary to calculate the clean water needs for Tauno Village in Oba Tengah District, Tidore Kepulauan City, which has a population of 516 people. The daily water requirement per person is 60 liters, resulting in a total village water demand of 32,506.85 liters. The total water requirement for all public facilities is 90,037.385 liters. Consequently, a 7,500 W pump with a flow rate of 400,000 liters per day and a head of 10 meters is selected to meet the clean water needs of Tauno Village. To supply power to the pump, 16 photovoltaic panels, each with a capacity of 1,200 Wp, are required.